Institutional Transformation Strategy for Local Culture-Based Community Empowerment: A Case Study of Kuntau Harimau Muda - M Lutfi Sasmila Wardana (Jurnal Locus Penelitian dan Pengabdian, 2026)
Contemporary shifts in development paradigms toward people-centered development have increasingly positioned local culture as a strategic asset for sustainable social empowerment, particularly at the grassroots level. However, grassroots cultural organizations often face managerial challenges that threaten their long-term institutional sustainability. This study examined the existing conditions, identified relevant internal and external factors, and formulated a strategy for local culture-based community empowerment through the traditional martial art of Kuntau at the Harimau Muda Community in Mandarsari, Banjar Regency. Guided by Edi Suharto’s empowerment dimensions (participation, access, control, and benefit) and employing SWOT matrix analysis to formulate strategic priorities, this qualitative study was conducted through sustained participatory observation, in-depth interviews with key informants (the Chairman, active members, community leaders, and the Head of Culture of the Banjar Regency Disbudporapar), and supporting documentation review. The findings revealed a significant managerial paradox: although the community has consistently achieved high and widely recognized regional accomplishments, its administrative operations remain largely informal, relying heavily on memory-based scheduling rather than documented management systems and depending on individual figures rather than institutional structures. The novelty of this research lies in demonstrating that institutional transformation—from figure-centered to system-centered governance—is a critical prerequisite for achieving sustainable culture-based community empowerment. The strategic formulation emphasizes the urgency of digitalizing administrative systems and formalizing institutional structures to strengthen the community’s bridging social capital with regional governments and formal economic networks. This study contributes to the development of institutional strengthening models for traditional martial arts communities and provides practical guidance for culture-based empowerment programs.